2001
DOI: 10.1029/2000wr900219
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of nitrogen transport in streams of the Lake Tahoe Basin, California‐Nevada

Abstract: Abstract. In an effort to characterize the spatial and temporal patterns of nitrogen concentration and load in streams of the Lake Tahoe basin, we analyzed 10 years of data from 10 streams, developing discharge-concentration relationships and total load estimates for nitrate-N, ammonium-N, and organic N. The results indicate that (1) most of the nitrate transport occurs early in the snowmelt season or during large winter rainstorms; (2) dissolved organic nitrogen concentrations peak early in the runoff season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 58 publications
3
24
3
Order By: Relevance
“…For example, N-rich compounds can originate in soils due to selective preservation of refractory proteins 42,43 and/or production of labile proteins in situ 41,42 and then be transported via runoff and stream flow. Terrestrial DON can sometimes account for up to 90% of the N that enters highelevation lakes 44,45 . However, accumulation of a protein-like fluorescence signal during warmer months has also been attributed to in situ production by lake microorganisms 9,19,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, N-rich compounds can originate in soils due to selective preservation of refractory proteins 42,43 and/or production of labile proteins in situ 41,42 and then be transported via runoff and stream flow. Terrestrial DON can sometimes account for up to 90% of the N that enters highelevation lakes 44,45 . However, accumulation of a protein-like fluorescence signal during warmer months has also been attributed to in situ production by lake microorganisms 9,19,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to roughly the same depth of a deep chlorophyll maximum that develops each summer at a depth of 55-70 m (TERC 2010). This high water transparency results from the relatively small watershed size (812 km 2 ) and low particulate and dissolved matter load in the associated tributaries flowing into the lake (Coats and Goldman 2001;Hatch et al 2001;Reuter et al 2003).…”
Section: Study Sitementioning
confidence: 99%
“…Jassby et al (1994) found that atmospheric deposition supplies most of the N to Lake Tahoe. While runoff from catchment streams supplies organic N to Lake Tahoe (Coats and Goldman 2001), a recent meta-analysis fi nds little relation between DON runoff and atmospheric N deposition (Pellerin et al 2006).…”
Section: Observed Biotic Responses To N Depositionmentioning
confidence: 99%